Delay-Sensitive Multi-Sensor Routing Scheduling Method for Underground IoT in Mines - Yinghui Zhang; Mingli Liu; Aiping Tan (Sensors)
Recently, there has been a growing interest in underground construction safety, during activities such as subway construction, underground mining, and tunnel excavation. While Internet of Things (IoT) sensors help to monitor these conditions, large-scale deployment is limited by high power needs and complex tunnel layouts, making real-time response a critical challenge. A delay-sensitive multi-sensor multi-base-station routing scheduling method is proposed for the IoT in underground mining. First, a mixed network topology of wireless and wired networks is formed based on the irregular distribution characteristics of multiple tunnels in the mine construction environment. Based on this topology, a multi-sensor and multi-base-station real-time routing scheduling problem is proposed, proving that the problem is NP-hard. Secondly, the corresponding solving algorithms are designed based on the greedy strategy and the heuristic strategy. Finally, an experimental platform is built, and the performance of the proposed algorithm is compared and analyzed.